UPAYA ORANG TUA MENUMBUHKEMBANGKAN BAKAT ANAK DALAM BIDANG KESENIAN DI SEKOLAH DASAR NEGERI 22 DESA TANAH KERAS KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Darnawita, Wenny; k, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
The problem in this study is how the efforts of parents children develop talents in the arts. This study aims to describe how efforts to develop the talents of children of parents in the arts can be seen from (1) the efforts of parents in understanding the characteristics of young talent in the arts. (2) the efforts of parents to guide and develop young talent in the arts. This research is a descriptive study sought to describe a situation for what it is or the truth. The population in this study were the parents of the students at SDN 22 Tanah Keras Kecamatan Bayang Kabupaten Pesisir Selatan, amounting to 96 people from classes I-VI. This study uses a sampling technique with purposive sampling based sampling considerations by researchers sampled only the upper class IV-VI which amounted to 51 people. The type of data in this study is the data interval, while the source of the data in this study were the parents of the students at SDN 22 Tanah Keras. Results of this study found that parents in an effort to understand the characteristics of young talent in both art categorized, and the efforts of parents in guiding and developing young talent in the arts well categorized. So it can be described in general of the research effort to develop the talents of children of parents in the arts well categorized. The authors suggest to students may always be a child who is full of creativity and develop talents and interests that exist in the child in accordance with their capabilities, as well as to parents increase effort has been given to children to encourage children to be more advanced in developing talent and creativity.